Self differential GNSS for synthetic aperture radar. Implementation and evaluation of a GNSS method for obtain ing a relative position estimation of an airborne synthetic aper ture radar - Englund, Erik; Johansson, Daniel (My University, 2022)
Obtaining an accurate position while using global navigation satellite systems (GNSS) signals, for example the global positioning system (GPS) can be useful for various applications. In this study a self-differential GNSS method called time-differenced carrier phase (TDCP) is evaluated as a measure of acquiring a precise position of a GNSS receiver mounted on a helicopter. The derived position from this method is used to produce synthetic aperture radar (SAR) images with a radar system developed by Saab AB called CARABAS-3 (VHF-band). A high accuracy of the helicopter’s flight path yields SAR images with higher focus and thus, contain more information about the desired target area. The most common method used for cal culating such a position is called real time kinematic (RTK) which relies on ground based reference stations that are placed in the vicinity of the planned flight path in order to differentiate and correct for the impact of atmospheric delay among other system derogating effects. These reference stations limit the mobility of the sys tem, since they need to be manually placed prior to flight. However, the TDCP method eliminates the need for these reference stations by using self-differentiation. A prominent difference between these methods is that in RTK the position is de rived as an absolute value but with TDCP the position is relative former positions. If this relative position is accurate to the real flight path but with a constant bias it will still be admissible for SAR processing and it will not affect the focus of the im age. The method has been implemented in Matlab and Python and compared with RTK processed flight paths of the helicopter in order to evaluate the performance of the method. The TDCP method effectively removes the need for the reference sta tions while having a median drift of less than 100 mm in each dimension compared to the RTK solutions, which is sufficient for focusing radar images taken with the CARABAS-3 system. For higher frequency (microwave) SAR systems, TDCP can aid automatic focusing algorithms (autofocus), by improving initial estimates of the synthetic aperture and hence reducing the computational demands.
Keywords: TDCP, RTK, GNSS, GPS, CARABAS-3, SAR, flight path, self-differencing, sp3, broadcast orbits, autofocus